(untitled) (Journal of humanities and social sciences exploratio, 2025)
Patriarchy exists as a dominant feature in the gender system of traditional Chinese culture, and it often obscures other dimensions within this system. Religious belief practices, as a reflection of social ideology, provide us with a new perspective to re-examine the gender system. The gender transformation of Guanyin (Avalokiteśvara Bodhisattva) and goddess worship can be regarded as an entry point to challenge the traditional gender narrative. Based on religious studies and gender studies, this paper systematically examines the evolutionary trajectory of Guanyin’s gender transformation from male to female. By analyzing materials such as historical documents, textual records, sculptural art, and folk tales, it reveals various factors behind Guanyin’s gender reconstruction. Meanwhile, this paper seeks to provide a new interpretive perspective for understanding the construction of gender symbols in Chinese culture and the belief practices in the interaction between religion and social gender.